2018
DOI: 10.1002/hep.30075
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Recruitment Domain Protein 6 Protects Against Hepatic Steatosis and Insulin Resistance by Suppressing Apoptosis Signal–Regulating Kinase 1

Abstract: The rapidly increasing prevalence of metabolic disorders associated with nonalcoholic fatty liver disease (NAFLD) warrants further study of the underlying mechanisms to identify key regulators as targets for the development of therapeutic interventions. Caspase recruitment domain protein 6 (Card6), as a member of the CARD family that regulates cell death and immunity, may potentially control this process. Indeed, Card6 down-regulation was found to be closely associated with the fatty livers observed in NAFLD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…ASK1 is a MAPK kinase kinase that was identified as an activator of the MKK4/7–JNK and MKK3/6–p38 pathways, resulting in apoptosis . Recently, a large number of studies have indicated a critically exacerbated role of ASK1 activation in the progression of NAFLD and NASH . Importantly, hyperactivated ASK1 was detected in human subjects with NASH, which further supports the potential clinical use of ASK1 as a therapeutic target for NASH.…”
Section: Discussionmentioning
confidence: 76%
“…ASK1 is a MAPK kinase kinase that was identified as an activator of the MKK4/7–JNK and MKK3/6–p38 pathways, resulting in apoptosis . Recently, a large number of studies have indicated a critically exacerbated role of ASK1 activation in the progression of NAFLD and NASH . Importantly, hyperactivated ASK1 was detected in human subjects with NASH, which further supports the potential clinical use of ASK1 as a therapeutic target for NASH.…”
Section: Discussionmentioning
confidence: 76%
“…Liver histology indicated that oral feeding of CT improved liver lobular structure and attenuated liver cell steatosis. There were no significant alterations of serum ALT or AST levels among the three groups, although there was a slight increase in serum ALT and AST levels (within a normal range of variation [35,36]) from the NC group relative to the HL and CT groups. These data indicated that there was no damage to liver function after oral administration of CT to reduce serum lipid levels.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, CARD6 was reported to protect against cardiac hypertrophy in response to pressure overload by regulating mitogen-activated protein kinases (MAPKs) signaling pathway [17]. Furthermore, CARD6-knockout mice exhibited severer fatty livers, which was partly associated with the excessive activation of NF-κB signaling [19]. Similarly, CARD6 efficiently protected against hepatic I/R injury through decreasing the release of inflammatory cytokines, blocking NF-κB signaling and ameliorating the cell death [18].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive inflammation is involved in SCI progression, and CARD6 was previously suggested to modulate inflammatory response [18,19]. Thus, we subsequently attempted to explore if CARD6 could modulate inflammation to regulate SCI development.…”
Section: Card6 Knockout Accelerates Inflammatory Response In Mice Aftmentioning
confidence: 99%